Knowledge regarding palliative care amongst medical and dental postgraduate students of medical university in western Maharashtra, India - Purushottam A Giri; Deepak B Phalke (Wolters Kluwer Medknow Publications, 2014)
Background: Palliative care is a relatively new field of medicine. The goal of palliative care is not to cure, but to provide comfort and maintain the highest possible quality of life for as long as life remains. However, there is a paucity of studies on knowledge among postgraduate students from medical and dental disciplines. Objectives: The present study was conducted to assess the knowledge about palliative care amongst postgraduate students of Medical University in Western Maharashtra. Materials and Methods: A cross-sectional study was conducted amongst a total of 178 postgraduate students which includes 112 medical and 66 dental disciplines of Medical University in Western Maharashtra during the period of June-August 2013. Data was analyzed in the form of percentage and proportions and Chi-square test was applied whenever necessary. Results: In the present study, 42.1% students didn't know the concept of 'autonomy' in palliative care, while 107 (60.1%) of students believed that most preferable route of administration in palliative care for treating chronic cases is oral. Among medical students 41.6% had shown overall good level of knowledge, while only 16.6% of dental students showed overall good level of knowledge. There was a significant difference found in the level of knowledge among the postgraduates between two disciplines. Conclusion: The study revealed the inadequacy in knowledge amongst postgraduate students of both disciplines; however knowledge level of dental was poor as compared to medical students. There is need to introduce palliative care in postgraduate curriculum of all health professional education.